Public Awareness Assessment: regarding Qualified and Unqualified Dental Practitioners. What difference does it makes in Treatment Outcome (Medical Forum Monthly, 2024)
Objective: An increasing number of unqualified dental practitioners in Pakistan are risking public, who say that so called doctors, are playing with patients heath and lives. Unqualified practitioners not only fail to provide relief to patients but also contributes to spread of diseases e.g. Hepatitis C because of the use of infected syringes and delay in reaching appropriate diagnosis with generating misconceptions in public regarding health issues. There is need to create public awareness about health risks incurred when people visits unqualified dental practitioners. Study Design: descriptive type of study survey. Place and Duration of Study: This study was conducted at Dental OPDs at LUMHS Jamshoro /Hyderabad and different private clinics at Jamshoro/Hyderabad during the months of October to December, 2012. Materials and Methods: We did assessment on the awareness level in people of Jamshoro/Hyderabad, regarding qualified and unqualified dental practitioner and what difference does it makes in treatment outcome. To a sample comprising of 3087 individuals, an assessment questionnaire comprising twelve items related to the objectives was developed and administered for survey. Data is analyzed using SPSS 17 application software. Results: The questionnaire was responded by 3059 individuals. Response rate was 99.09%, among respondents 53% males and 47% females. Only 68.7 % patients reported that they were aware of difference in qualified and unqualified dental practitioners, 56% individuals reported that they ask about qualification of dental of practitioner before treatment whether he is qualified or unqualified, 43% individuals reported that qualified dental practitioner’s treatment is better outcome, 29% individuals reported treatment outcome more or less similar whether it qualified or unqualified, 24% individuals reported that unqualified dental practitioner’s treatment is better outcome.66% individuals reported that they like to visit unqualified dental practitioner because of socio-economic reasons, 23.6% individuals reported that they like to visit unqualified dental practitioner because they feel more comfortable, 10.4% individuals reported that they like to visit unqualified dental practitioner because of unavailability of qualified dental practitioners in their areas. Conclusion: Especial awareness campaigns should be launch to ensure that the masses refrain from going to unqualified dental practitioners. We can help out concerned authorities to play their role to curb the practices of unqualified dental practitioners.